PERFORMATIVITAS DALAM MANGA SHONEN-AI: SEKAIICHI HATSUKOI, HENSHIN DEKINAI DAN HIMANANODE HAJIMETE MIMASHITA - Ni Made Savitri Paramita (POETIKA, 2014)
This research underlies the analysis on the performance and performativity of characters in shonen-ai: Sekaiichi Hatsukoi, Henshin Dekinai, and Himananode Hajimete Mimashita manga. Characterization in shonen-ai manga is based on the characters’ role within the same-sex relationship, which are the male role (seme) and the female role (uke). The character of Seme tends to be aggressive, protective, smart, good looking, and unemotional. On the other hand, Uke is feminine, smaller, physically weak, insecure, and emotional. The writer would like to analyze whether performance align with performativity based on the characterization of seme and uke. Judith Butler’s Performativity is used as theoretical framework within the research. The theory covers gender, performance, and performativity. Gender as social construction is fluid and unbound to the body. This phenomenon is seen in these three shonen-ai manga. Character that looks masculine does not always have the male role (seme) and the feminine one does not always have the female role (uke). Physical performance is not merely associated with gender (performativity).Keywords: shonen-ai manga, same-sex relationship, performativity, gender.